Simulation Modeling and Analysis: A Collateral Application and Exposition of RFID Technology - Amini, Mehdi; Otondo, Robert F.; Janz, Brian D.; Pitts, Mitzi G. (Production and Operations Management, 2007)
RFID technology provides in‐depth, real‐time visibility into the status of assets throughout the supply chain. However, the deployment of RFID technology may have collateral value in the high‐quality data generated by these assets. This study explores the potential value of RFID data for tactical and strategic purposes and the redesign of processes within supply chain through the deployment of simulation modeling and analysis. We present a simulation study conducted at a regional hospital for which data related to trauma patient movement was collected with an RFID‐based system. We find that not only does this data serve as the basis for successful simulation modeling, but that RFID technology may address several data‐related challenges previously identified in the simulation literature.